Prostate cancer multidisciplinary care: improving patient outcomes. Issue 4 (July 2015) - Dundee, Philip E.; Wong, Lih-Ming; Corcoran, Niall; Wootten, Addie C.; Crowe, Helen; Sandall, David; Dowrick, Adam; Bowden, Patrick; Tran, Ben; Crowe, Jane; O'Sullivan, Richard; Ryan, Andrew; et al.
<x xml:space="preserve">Abstract</x> Multidisciplinary care should serve to improve communication between specialists and ensure that prostate cancer patients receive optimal care based on best practice and evidence‐based guidelines. Here, the authors describe the implementation of this model in a prostate cancer‐specific clinic in Australia.